2015
DOI: 10.1111/ter.12133
|View full text |Cite
|
Sign up to set email alerts
|

The key role of global solid‐Earth processes in preconditioning Greenland's glaciation since the Pliocene

Abstract: After >500 Ma of absence, major Northern Hemisphere glaciations appeared during the Plio‐Pleistocene, with Greenland leading other northern areas. Here, we propose that three major solid‐Earth processes underpinned build‐up of the Greenland ice‐sheet. First, a mantle‐plume pulse, responsible for the North Atlantic Igneous Province at ~60 Ma, regionally thinned the lithosphere. Younger plume pulses led to uplift, which accelerated at ~5 Ma, lifting the parts of the East Greenland margin closest to Iceland to el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 51 publications
5
41
1
Order By: Relevance
“…S7). This is in agreement with previous work from the broader region (Steinberger et al, 2015;Marquart and Schmeling, 2004) and suggests dynamic surface uplift for southwestern Norway within the last 10 Myr, with an increasing trend toward the coast, and concurrent dynamic subsidence that increases toward the east (Fig. 4D, Fig.…”
Section: Resultssupporting
confidence: 91%
“…S7). This is in agreement with previous work from the broader region (Steinberger et al, 2015;Marquart and Schmeling, 2004) and suggests dynamic surface uplift for southwestern Norway within the last 10 Myr, with an increasing trend toward the coast, and concurrent dynamic subsidence that increases toward the east (Fig. 4D, Fig.…”
Section: Resultssupporting
confidence: 91%
“…The four predictions of DT change from Rowley et al (2013) are reproduced on each frame. In addition, we also show the recent prediction by Steinberger et al (2015), which is based on a viscosity and density model that is derived from the Grand tomography model ( Steinberger et al, 2015). This prediction is amongst a group of models that predict long-term subsidence of the whole US East coast (Müller et al, 2008;Spasojevic et al, 2008); such models are difficult to reconcile with the observed extent of Pliocene flooding of the ACP since they would require a significantly higher degree of melting during the Pliocene than previously thought (i.e., essentially the disappearance of all ice sheets and glaciers).…”
Section: Accepted Manuscriptmentioning
confidence: 90%
“…Moucha et al, 2008;Müller et al, 2008;Spasojevic et al, 2008;Rowley et al, 2013;Flament et al, 2013;Steinberger et al, 2015). In contrast to site-specific paleo sea-level records, the mid-Pliocene shoreline along the ACP is a powerful constrain on geophysical models because it displays differential uplift that is independent of the eustatic sea-level change from the mid-Pliocene to present-day.…”
Section: Accepted Manuscriptmentioning
confidence: 93%
“…However, numerical simulations suggest that high-latitude cooling may also occur without the closure of the Panama gateway (e.g., Maier-Reimer et al, 1990;Murdock et al, 1997). An additional hypothesis is that Cenozoic true polar wander-the rotation of the Earth and mantle relative to the spin axis in response to change in solid Earth density distributions-may have preconditioned the northern Atlantic for glaciation (Steinberger et al, 2015).…”
Section: Tectonic Influence On the Ocean And Atmosphere Circulation Pmentioning
confidence: 99%